Prevalence of mixed genotype hepatitis C virus infections in the UK as determined by genotype‐specific PCR and deep sequencing. Issue 5 (21st February 2018) - McNaughton, A. L.; Sreenu, V. B.; Wilkie, G.; Gunson, R.; Templeton, K.; Leitch, E. C. M.
Summary: The incidence of mixed genotype hepatitis C virus (HCV) infections in the UK is largely unknown. As the efficacy of direct‐acting antivirals is variable across different genotypes, treatment regimens are tailored to the infecting genotype, which may pose issues for the treatment of underlying genotypes within undiagnosed mixed genotype HCV infections. There is therefore a need to accurately diagnose mixed genotype infections prior to treatment. PCR‐based diagnostic tools were developed to screen for the occurrence of mixed genotype infections caused by the most common UK genotypes, 1a and 3, in a cohort of 506 individuals diagnosed with either of these genotypes. The overall prevalence rate of mixed infection was 3.8%; however, this rate was unevenly distributed, with 6.7% of individuals diagnosed with genotype 3 harbouring genotype 1a strains and only 0.8% of samples from genotype 1a patients harbouring genotype 3 ( P < .05). Mixed infection samples consisted of a major and a minor genotype, with the latter constituting less than 21% of the total viral load and, in 67% of cases, less than 1% of the viral load. Analysis of a subset of the cohort by Illumina PCR next‐generation sequencing resulted in a much greater incidence rate than obtained by PCR. This may have occurred due to the nonquantitative nature of the technique and despite the designation of false‐positive thresholds based on negative controls.